MEMAHAMI MODEL KONSEP DASAR KURIKULUM - Fitri Cecilia Oktaviani; Ririn Padilah, Yeni (ADISAM PUBLISHER, 2026)
Curriculum in education has been a concern since the classical greek period as stated by robert.s.of educational reseaarch that at time plato had compiled arithmetic as a summary of learning which included geometry astranomy and geometry all of which were releted to mathematics lessonsn the next curriculum is more real and conceptualized in education